Pendayagunaan Kohesi Sosial Petani Perempuan Single Parent di Kabupaten Muna Barat - Mursin; febrina, Fitrah; Nur, Nurwiati (Universitas Cenderawasih, 2024)
This article aims to explore the form of social cohesion of single parent female farmers. This research uses qualitative descriptive ethnographic methods. The location of this research is SangiaTiworo Village, South Tiworo District, West Muna Regency, Southeast Sulawesi Province. The data collection used was interview and observation methods. Data analysis techniques refer to data analysis models consisting of data reduction, data presentation, and drawing conclusions/verification. The results of this research are that as single parent female farmers, the bonds of solidarity built by fellow farmers become their social glue capital to be enthusiastic in managing their agricultural land, especially patchouli plants (PogostemonCablin Benth), this is also supported by the spirit of mutual cooperation among patchouli farmers (PogostemonCablin Benth) starting from working together in land clearing, seeding, plant care, harvesting to post-harvest. This is what supports them to continue trying to develop their agricultural land even as single parent women. Apart from building social solidarity, which is accompanied by a spirit of mutual cooperation, fellow farmers also need a work ethic. Because this work ethic is the determinant of success, such as applying the principles of hard work, respecting time, having a proactive attitude in agricultural matters, honesty, openness to each other, a sense of responsibility and commitment that is continuously upheld.